2021
DOI: 10.1038/s41598-021-84108-w
|View full text |Cite
|
Sign up to set email alerts
|

The rule of brain hematoma pressure gradient and its influence on hypertensive cerebral hemorrhage operation

Abstract: To comparatively study the size of and variation in the ‘brain-haematoma’ pressure gradient for different surgical methods for hypertensive intracerebral haemorrhage (HICH) and analyse the gradient’s influence on surgical procedures and effects of the haemorrhage. Seventy-two patients with HICH treated from 1/2019 to 12/2019 were randomly divided into two groups, namely, the keyhole endoscopy and large trauma craniotomy groups, according to different operative methods. Intraoperative changes in intracranial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…reduction also played a significant role in improving intracranial hemodynamic measures. Sun et al investigated intraoperative changes in ICP to calculate intraoperative alterations in the "brain-hematoma" pressure gradients (14). Patients undergoing large trauma craniotomy had rapid decreases in ICP and a small "brain-hematoma" pressure gradient after the hematoma was removed.…”
Section: Icp and Cpp Time Burden And Outcomesmentioning
confidence: 99%
“…reduction also played a significant role in improving intracranial hemodynamic measures. Sun et al investigated intraoperative changes in ICP to calculate intraoperative alterations in the "brain-hematoma" pressure gradients (14). Patients undergoing large trauma craniotomy had rapid decreases in ICP and a small "brain-hematoma" pressure gradient after the hematoma was removed.…”
Section: Icp and Cpp Time Burden And Outcomesmentioning
confidence: 99%
“…Rennert et al through the retrospective analysis of 23 cases of endoscopic treatment and 20 cases of microwindow craniotomy when treating cerebral parenchyma hemorrhage found that the prognosis of endoscopy group was remarkably better than craniotomy group [ 28 ]. Sun and other prospective studies compared the functional independence assessment (FIM) scale score, Barthel index score, and MP index at 6 months after operation [ 29 ]. It is concluded that neuroendoscopic surgery is more beneficial to the recovery of neurological function than craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The scores of physiological function, psychological function, social function, and health self-cognition in the research group were lower than the control group, and there were fewer postoperative complications. The reasons for this can be summarized as follows [ 29 ]. (1) Rapid decompression: the process of craniotomy in neuroendoscopic surgery is simplified, so most operations can be completed within 15 minutes for decompression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the development of smart healthcare has provided more possibilities for the application of seamless nursing. Characterized by digitalization, automation, and intelligence, the smart healthcare management platform can standardize the nursing information system and simplify the nursing management process, especially avoiding the potential safety hazards caused by human factors in nursing work and shortening the handover time of nursing staff [20][21][22]. e application of smart healthcare management in seamless nursing can effectively improve the efficiency of collaborative work among nursing staff and increase the timeliness and scientificity of nursing work.…”
Section: Discussionmentioning
confidence: 99%